1998
DOI: 10.1046/j.1365-201x.1998.0273f.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal nursing behaviour and the delivery of milk to the neonatal spontaneously hypertensive rat

Abstract: Fostering spontaneously hypertensive rat (SHR) pups to Wistar-Kyoto (WKY) dams permanently lowers their adult blood pressure. SHR dams show increased nursing behaviour and the SHR pup displays an exaggerated pressor response to milk ingestion. We have therefore measured pup feeding rates and dam milk secretion rates in SHR and WKY dams nursing natural and foster litters. Maternal behaviour displayed by SHR and WKY dams nursing natural or foster litters and the milk delivery rate to non-fasted pups were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 26 publications
2
43
0
Order By: Relevance
“…Though attractive, this hypothesis is not supported by our subsequent study of the maternal behaviour of foster dams (40). WKY dams rearing SHR foster litters increased their nursing behaviour, whereas SHR dams rearing WKY foster litters reduced the time spent in nursing postures, suggesting that the pup strain may influence the behaviour of the dam.…”
Section: Postnatal Programmingmentioning
confidence: 38%
See 4 more Smart Citations
“…Though attractive, this hypothesis is not supported by our subsequent study of the maternal behaviour of foster dams (40). WKY dams rearing SHR foster litters increased their nursing behaviour, whereas SHR dams rearing WKY foster litters reduced the time spent in nursing postures, suggesting that the pup strain may influence the behaviour of the dam.…”
Section: Postnatal Programmingmentioning
confidence: 38%
“…We (39,40) and others (41) have subsequently confirmed that cross-fostering SHR pups to WKY dams consistently lowers adult blood pressure by 20-30 mmHg. In the reverse experiment, cross-fostered normotensive WKY or Sprague-Dawley pups suckled by SHR dams did not develop elevated blood pressure at maturity (37,38).…”
Section: Postnatal Programmingmentioning
confidence: 83%
See 3 more Smart Citations